Verification analysis of an agent based model in behaviour change process - Ojeniyi, Adegoke; Ab. Aziz, Azizi; Yusof, Yuhanis (2015)
This paper describes the verification analysis for agent formal model of behaviour change process. The verification analysis was based on two widely used approaches in agent formal evaluation namely mathematical and automated analysis. The mathematical analysis made use of stability equilibria point while the automated, made use of Temporal Trace Language (TTL). The results obtained verify the formal model validity.